Comprehensive Analysis of Bacterial Community Structure and Diversity in Sichuan Dark Tea (Camellia sinensis) - Yan, Kuan; Yan, Linfeng; Meng, Lina; Cai, Hongbing; Duan, Ailing; Wang, Lian; Li, Quanzi; El-Sappah, Ahmed H.; Zhao, Xianming; Abbas, Manzar (Frontiers in Microbiology, 2021)
Bacteria and fungi present during pile-fermentation of Sichuan dark tea play a key role in development of its aesthetic properties such as color, taste and fragrance. In our previous study, high-throughput sequencing of dark tea during fermentation revealed Aspergillus was abundant but scarce knowledge is available about bacterial communities during pile-fermentation. In this study, we rigorously explored bacterial diversity in Sichuan dark tea at each specific stage of piling. Analysis of cluster data revealed; 2948 operational taxonomic units (OTUs), which were divided into 42 phyla, 98 classes, 247 orders, 461 families, 1052 genera, and 1888 species. Genus Certain members of the family Enterobacteriaceae was were dominant at early stages of fermentation YC, W1 and W2, while Pseudomonas at middle stage W3, and highest bacterial diversity was observed at final quality determining stage W4. Noticeably, probiotics such as Bacillus, Lactobacillus, Bifidobacterium and Saccharopolyspora were also significantly higher at quality determining stage W4. Our findings willmight help in precise bacterial inoculation for probiotic foods production by increasing health benefits of Sichuan dark tea. This research also falls under umbrella of “Establish Good Health and Well-Being” Sustainable Development Goals of United Nations Organization.